2016
DOI: 10.1111/iwj.12684
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of pyoderma gangrenosum with granulocyte and monocyte adsorption apheresis

Abstract: Pyoderma gangrenosum is a neutrophilic dermatosis clinically characterised by the presence of painful skin ulcerations with erythematous and undetermined borders and histologically by the presence of neutrophilic infiltrates in the dermis. Granulocyte and monocyte adsorption apheresis, also called granulocytapheresis, is a therapeutic strategy for extracorporeal immunomodulation that selectively removes activated granulocytes and monocytes/macrophages from the peripheral blood. Here, we report a case of a 73-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…AA remission can be induced without using steroids and sustained with GCAP and IFX. GCAP is reported to be useful for the treatment of IBD and PG (12,13). Indeed, Kato et al described a Japanese patient with AAs and Crohn's disease (CD) who showed improvement following treatment with GCAP (5).…”
Section: Discussionmentioning
confidence: 99%
“…AA remission can be induced without using steroids and sustained with GCAP and IFX. GCAP is reported to be useful for the treatment of IBD and PG (12,13). Indeed, Kato et al described a Japanese patient with AAs and Crohn's disease (CD) who showed improvement following treatment with GCAP (5).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments to control inflammation include topical agents (corticosteroids [13], tacrolimus [14], and cyclosporine [15]), intralesional agents (corticosteroids [16] and cyclosporine [17]), and systemic agents (oral corticosteroids [18], oral cyclosporine [15], and infliximab [19]). Other biologic agents (etanercept [20] and adalimumab [21]), granulocyte apheresis [22], and thalidomide [23] have been reported to have successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…oral corticosteroids, CsA, tacrolimus, colchicine, dapsone, MTX, intravenous immunoglobulin) and targeted therapy, including TNF-α inhibitors, anti IL-1 and IL-12/23 antagonists (42). Alternatively to current existing therapies, GMA is an effective option with minimal side effects, especially for steroid and immunosuppressant-resistant PG (43). Forty-nine cases of GMA application for PG have been summarized in Table II (28,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62).…”
Section: Application Of Gma In Neutrophilic Dermatosesmentioning
confidence: 99%
“…Alternatively to current existing therapies, GMA is an effective option with minimal side effects, especially for steroid and immunosuppressant-resistant PG (43). Forty-nine cases of GMA application for PG have been summarized in Table II (28,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). In the main case series, Higashi et al (44) reported a complete response in eight patients, a nearly complete response in three patients and a partial response in two patients.…”
Section: Application Of Gma In Neutrophilic Dermatosesmentioning
confidence: 99%